Virotherapy in Germany - recent activities in virus engineering, preclinical development, and clinical studies - Nettelbeck, Dirk M.; Leber, Mathias Felix; Altomonte, Jennifer; Angelova, Assia; Beil, Julia; Berchtold, Susanne; Delic, Maike; Eberle, Jürgen; Ehrhardt, Anja; Engeland, Christine E.; Fechner, Henry; Geletneky, Karsten; et al. (Viruses, 2021)
Virotherapy research involves the development, exploration, and application of oncolytic viruses that combine direct killing of cancer cells by viral infection, replication, and spread (oncolysis) with indirect killing by induction of anti-tumor immune responses. Oncolytic viruses can also be engineered to genetically deliver therapeutic proteins for direct or indirect cancer cell killing. In this review—as part of the special edition on “State-of-the-Art Viral Vector Gene Therapy in Germany”—the German community of virotherapists provides an overview of their recent research activities that cover endeavors from screening and engineering viruses as oncolytic cancer therapeutics to their clinical translation in investigator-initiated and sponsored multi-center trials. Preclinical research explores multiple viral platforms, including new isolates, serotypes, or fitness mutants, and pursues unique approaches to engineer them towards increased safety, shielded or targeted delivery, selective or enhanced replication, improved immune activation, delivery of therapeutic proteins or RNA, and redirecting antiviral immunity for cancer cell killing. Moreover, several oncolytic virus-based combination therapies are under investigation. Clinical trials in Germany explore the safety and potency of virotherapeutics based on parvo-, vaccinia, herpes, measles, reo-, adeno-, vesicular stomatitis, and coxsackie viruses, including viruses encoding therapeutic proteins or combinations with immune checkpoint inhibitors. These research advances represent exciting vantage points for future endeavors of the German virotherapy community collectively aimed at the implementation of effective virotherapeutics in clinical oncology.
Gesehen am 21.01.2022